Overexpression of Vimentin in Canine Prostatic Carcinoma - Rodrigues, M. M. P. [UNESP]; Rema, A.; Gaertner, F.; Soares, F. A.; Rogatto, Silvia Regina [UNESP]; De Mour, V. M. B. D.; Laufer-Amorim, R. [UNESP] (Elsevier B.V., 2011)
Canine prostatic tumours exhibit similarities to those of man and may represent a useful model system to explore the mechanisms of cancer progression. Tumour progression to malignancy requires a change from an epithelial phenotype to a fibroblastic or mesenchymal phenotype. Vimentin expression is associated with the invasive phenotype of human prostate cancer cells. The aim of the present study was to characterize immunohistochemically the expression of vimentin by canine prostatic carcinomas. Primary carcinomas and metastatic tumour foci both showed vimentin expression. This finding suggests that the acquisition of the epithelial-mesenchymal transition phenotype in canine prostatic carcinoma may be characterized by the presence of mesenchymal intermediate filament (vimentin) that could lead to a higher likelihood of metastasis. Published by Elsevier Ltd.
Keywords: dog; prostate carcinoma; vimentin